Pengaruh Audit lag, Audit Tenure, Financial Distress, Dan Ukuran Perusahaan Terhadap Opini Audit Going Concern - Dhika Arief Kusuma; Andri Syahputra (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to analyze and test the influence of audit lag, audit tenure, financial distress, and company size on audit opinion going concern. The type in this study is quantitative. The population of this study was conducted on energy sector companies listed on the Indonesia Stock Exchange (IDX) in 2019-2023. The type of data used is secondary data. The sampling technique was carried out using the purposive sampling technique. The total population in the study was 82 companies and the sample obtained was 57 companies. The research data analysis technique used in this study is logistic regression using the Eviews 12 application. The results of this study show that simultaneously audit lag, audit tenure, financial distress and company size affect the opinion of audit going concern. The results of the study partially audit lag (X1) affect the opinion of the audit going concern. Audit tenure (X2) has no effect on the audit opinion going concern. Financial distress (X3) affects the audit opinion going concern. Company Size (X4) affects the audit opinion going concern.